2019
DOI: 10.5888/pcd16.190117
|View full text |Cite
|
Sign up to set email alerts
|

Gardening for Health: Using Garden Coordinators and Volunteers to Implement Rural School and Community Gardens

Abstract: Gardens provide access to healthy food, increase access to nutrition and physical activity opportunities, and are a focal point for community interventions. We used a gardening intervention to improve local access to and consumption of fruits and vegetables and as an integral part of overall efforts of local wellness coalitions. Seasonal garden coordinators were hired, and action plans included goals for nutrition and physical activity education programs and youth and adult engagement. The characteristics of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…A motivated student/group of students can run a programme for a while; however, once these students graduate or move on, if a line of succession is not established then a programme can quickly fall into disorder. This has been evidenced in garden programmes where a dedicated garden coordinator is needed for the sustainability of the community, school or campus‐based gardens (Stluka et al, 2019; Ullevig et al, 2021). The responsibility of the programmes or where the programme was housed on campus could determine the availability of staff oversight, resources and funding.…”
Section: Discussionmentioning
confidence: 99%
“…A motivated student/group of students can run a programme for a while; however, once these students graduate or move on, if a line of succession is not established then a programme can quickly fall into disorder. This has been evidenced in garden programmes where a dedicated garden coordinator is needed for the sustainability of the community, school or campus‐based gardens (Stluka et al, 2019; Ullevig et al, 2021). The responsibility of the programmes or where the programme was housed on campus could determine the availability of staff oversight, resources and funding.…”
Section: Discussionmentioning
confidence: 99%
“…However, such an intervention may have limited value in urban areas due to complications surrounding land pressures, hygiene, disease spread and environmental pollution [ 49 , 50 ]. Related to this are the existing interventions that give households or communities the resources to grow their own food in local gardens [ 51 , 52 ]. In this study, no association was found between growing food and household food insecurity, individual dietary diversity, or individual BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Local food systems are complex webs of actors and activities involved in food procurement, distribution, processing/preservation, consumption, and disposal at the community or regional level (Edge, 2013). Some common examples of interventions aimed at strengthening LFSs include financial vouchers for beneficiaries to purchase healthy food through farmers' or community markets (Dimitri et al, 2014;Community Food Centres Canada, 2018); school and community garden programs (Stluka et al, 2019); and incentives for local food growers to manage food production costs, raise their income, and pass savings onto people (Sitaker et al, 2014). Such interventions are concentrated within the food procurement, distribution, and consumption components of LFSs and often target behavioral change in individuals, whereby people are expected to make healthy food choices.…”
Section: Introductionmentioning
confidence: 99%